2018
DOI: 10.1177/1049732318755675
|View full text |Cite
|
Sign up to set email alerts
|

“Life Goes On.” Everyday Tasks, Coping Self-Efficacy, and Independence: Exploring Older Adults’ Recovery From Hip Fracture

Abstract: Older adults face many challenges in the first few months after hip fracture. Rehabilitation holds promise to assist the recovery process. Therefore, we used semistructured interviews to explore older adults' and allied health professionals' acceptance of a rehabilitation intervention for hip fracture, and we described perceptions of the early recovery period (<4 months). Interviews were recorded and transcribed verbatim; three authors independently read the transcripts multiple times and together developed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(48 citation statements)
references
References 33 publications
1
45
0
Order By: Relevance
“…Thus, healthcare providers should develop individualized health education plans for the long-term rehabilitation of patients with hip replacements even before their discharge from the hospital [30]. The rehabilitation plan should be deployed beginning with patient’s admission to home-based rehabilitation; moreover, adequate evaluation and supervision are required to ensure the effectiveness of rehabilitation [31, 32].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, healthcare providers should develop individualized health education plans for the long-term rehabilitation of patients with hip replacements even before their discharge from the hospital [30]. The rehabilitation plan should be deployed beginning with patient’s admission to home-based rehabilitation; moreover, adequate evaluation and supervision are required to ensure the effectiveness of rehabilitation [31, 32].…”
Section: Discussionmentioning
confidence: 99%
“…Walking seems to be the most existential mobility activity according to our participants, and their testimony was that they would fight to maintain this ability. Langford et al (2018) also found walking to be the most frequent mentioned kind of activity among a group of older adults after suffering a hip fracture. To understand the existential meaning of walking, we can turn to the individuals' responses to the loss of this ability-caused in this study by a hip fracture-because the ability to walk is seldom reflected upon until walking difficulties occur (Martinsen et al, 2018).…”
Section: The Connection Between Mobility and Self-imagementioning
confidence: 88%
“…Hip fractures represent a major problem in the health care service with a mortality rate of 5% to 10% during the first month and 20% to 30% during the first year after the fracture (Sogaard et al, 2016). After suffering a hip fracture, individuals often have poorer strength, mobility and balance (Madsen et al, 2000;Visser et al, 2000), as well as reduced quality of life (Amarilla-Donoso et al, 2020;Sihvonen et al, 2009) and independence (Langford et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Support from health professionals provides not only information and exercises but also emotional and motivational support and confidence boosting. Support from informal caregivers, family and friends is also seen as invaluable to help with ADLs, emotional support, encouragement and companionship [95,102,103]. Thus, inclusion of psychological and social interventions in hip fracture rehabilitation programmes is likely to be beneficial.…”
Section: Psychosocial Factors and Rehabilitationmentioning
confidence: 99%